Effect of storage conditions on seed germination behaviour of Parkia roxburghii G. Don under nursery conditions - Leishangthem, Chanu Langlentombi; Ziipoa, Benjamin Ng Nakho; Singh, Nongmaithem Raju (Indian Journal of Agroforestry, 2020)
The present study was conducted in Dr Y S Parmar University of Horticulture and Forestry, Nauni, Solan. Seeds were stored at ambient temperature 9.85-23.70°C (T1), 5°C (T2) and -5°C (T3) in three different containers i.e., pottery pot (C1), airtight plastic container (C2) and canvas bag (C3) for a period of 6 months. Germination tests were conducted at two months interval. The germination trials were carried out in polyhouse by sowing the seeds in polybags containing the medium soil and sand (1:1) in a Randomized Block Design (factorial). The seeds stored at 5°C (T2) in airtight plastic container (C2) maintained 50% germination, 20% germination energy and 4.40 germination value till 6 months of storage. The study reveals that P. roxburghii seeds are comparatively short-lived if stored at a low temperature of -5°C in a canvas bag. The best efficiency method for storing seeds of P. roxburghii is to store the seeds at 5°C in airtight plastic container with low moisture content (10.96%) inorder to maintain longer viability.